Worldview Islam sebagai Framework Filsafat Islam Hakikat, Idealisme dan Realitas - Kardiyanto, Wawan (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
This article aims to explain the worldview of Islam as a framework of Islamic philosophy of essence, idealism and reality by using comparative methodology between Islam and the West (orientalist). According to the theory of the worldview Alparslan, the inability to absorb sophisticated Greek thought (sophisticated reading) is due to the poor mechanism to produce a scientific conceptual scheme in the view of life. Peters facts that Christians can not complete the translation of Organon are understood in the perspective of the worldview of Islam. The concept of Western scholarship came after they came into contact with Muslim civilization. This process is recognized by other Western writers as "appropriaing and developing" the Greek tradition into the "Islamic cultural milieu". The results of this study indicate that the framework of Islamic philosophy study not only talks on the level of nature and idealism, but also had to do research in this discourse by looking at the reality of the concept framework of Islamic philosophy study applied to IAIN in Indonesia.